2013
DOI: 10.1017/s1751731112002005
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of chromogranin A in porcine saliva: validation of a time-resolved immunofluorometric assay and evaluation of its application as a marker of acute stress

Abstract: The objective of this study was to develop and validate a time-resolved immunofluorometric assay (TR-IFMA) for porcine salivary chromogranin A (CgA) measurements, using a species-specific antibody, and evaluate its behaviour in an acute stress model. Polyclonal antibodies were produced in rabbits immunized with a synthetic porcine fragment of CgA 3592379 and used to develop a sandwich TR-IFMA. This TR-IFMA was analytically validated and showed intra-and inter-assay coefficients of variation of 6.23% and 5.82%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 37 publications
5
78
0
3
Order By: Relevance
“…A previous study showed that CgA concentrations in human saliva are elevated under stress (Nakane et al, 2002). Another study showed that CgA concentration in saliva also increased after an acute stress situation in pigs (Escribano et al, 2013). Yet Kanno et al (1999) showed that an isolated rat submandibular gland perfused with noradrenaline at 1 mM produced a marked increase of CgA concentration in saliva, whereas further increases in the noradrenaline concentration (10 or 100 mM) yielded a concentration-dependent decrease.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study showed that CgA concentrations in human saliva are elevated under stress (Nakane et al, 2002). Another study showed that CgA concentration in saliva also increased after an acute stress situation in pigs (Escribano et al, 2013). Yet Kanno et al (1999) showed that an isolated rat submandibular gland perfused with noradrenaline at 1 mM produced a marked increase of CgA concentration in saliva, whereas further increases in the noradrenaline concentration (10 or 100 mM) yielded a concentration-dependent decrease.…”
Section: Discussionmentioning
confidence: 97%
“…The release of CgA in saliva is mediated by the secretion of catecholamines [75], and has been related to the activation of SAM [76]. In humans, the measurement of CgA in saliva has been used as a reliable marker of SAM activation as an alternative to adrenaline and noradrenaline [77], which have high variability in results and low stability in saliva [7880]. …”
Section: Biomarkers Of Stress Studied In Pigsmentioning
confidence: 99%
“…In pig, CgA has been used as a marker of SAM activation in different situations such as immobilization with a nasal snare [80], after refeeding following a period of food deprivation [25] and after isolation or regrouping [63]. CgA is not affected by age, gender or circadian rhythms [81].…”
Section: Biomarkers Of Stress Studied In Pigsmentioning
confidence: 99%
“…These gregarious, inquisitive animals demonstrate sophisticated social behaviour [36,51], as well as consistent differences between individuals in behavioural responses to novelty [26,40]. Salivary cortisol has been assayed extensively in pigs [20,32,52] and, recently, pigs have been shown to produce measurable increases in the sympathetic markers, sAA [28] and CgA [21], in response to a stressor. The aim of the current study was to investigate the existence of consistent inter-individual variation in exploratory behaviour and reactivity of the two major stress systems, and describe their relationship.…”
Section: Current Studymentioning
confidence: 99%
“…We shipped samples on dry ice to Salimetrics LLC for analysis via enzyme immunoassay for sAA, cortisol, and CgA. Saliva flow rate was not measured, as valid measurements of our analytes of interest can be obtained without the need for assessing flow rate (sAA: [65]; cortisol: [81]; CgA: [21]). …”
Section: Saliva Samplingmentioning
confidence: 99%